1998
DOI: 10.1021/ja981650u
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Peptide Hydrolysis by Thermolysin. A Semiempirical and QM/MM Study

Abstract: The hydrolysis by thermolysin of formamide, considered as a model of a peptide bond, has been studied with semiempirical and mixed QM/MM methods. The study has been carried out for two catalystsa molecular complex of a Zn2+ ion with two imidazole molecules and a formate ion, modeling the active site of the enzyme, and the whole enzymeand for two mechanisms involving one and two water molecules. In every case, the first step of the reaction is a nucleophilic attack of the carbon atom by the oxygen of a water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 65 publications
(46 reference statements)
1
48
0
Order By: Relevance
“…Protonation states of charged residues in the enzyme complex were determined via H++ program42 and by carefully examining local hydrogen bond networks. In all TLN models, His142 and His146 was identified as singly protonated, whereas His231 was doubly protonated, which are the same as previous studies43,44. For HDAC8 models, His180 was determined as singly protonated on δ site, while His142 and His143 were determined as singly protonated on ε site.…”
Section: Methodssupporting
confidence: 66%
“…Protonation states of charged residues in the enzyme complex were determined via H++ program42 and by carefully examining local hydrogen bond networks. In all TLN models, His142 and His146 was identified as singly protonated, whereas His231 was doubly protonated, which are the same as previous studies43,44. For HDAC8 models, His180 was determined as singly protonated on δ site, while His142 and His143 were determined as singly protonated on ε site.…”
Section: Methodssupporting
confidence: 66%
“…The very simple model used here to represent this reaction does not take into account finer effects such as polarization of the substrate (due the metal center and its ligands [37] ) or a stabilizing role due to molecular recognition. All these contributions could energetically favor the feasibility of the reactions described above, but keeping in mind that electron transfer is often the most energetic Our results have also shown that quercetin oxygenolysis should proceed by 1,3-cycloaddition, despite the fact that 1,2-cycloadditions are less energy demanding.…”
Section: Discussionmentioning
confidence: 99%
“…Their results 55 suggest that the rate determining step is the formation of a tetrahedral intermediate arising from the attack of a Zn-coordinated OH group on the carbonyl of the substrate. A semiempirical and QM/MM study of peptide hydrolysis by thermolysin was performed by Rivail 56 and co-workers while Giessner and Jacob 57 employed MNDO (with special Zn parameterization) to calculate the interactions between zinc and different ligands at the thermolysin active site. Goldblum and co-workers performed a semi-empirical QM study on the alternative mechanisms for zinc proteinases 5860.…”
Section: Introductionmentioning
confidence: 99%